2005
DOI: 10.1177/107110070502600609
|View full text |Cite
|
Sign up to set email alerts
|

Results of an Internet Survey Determining the Most Frequently Used Ankle Scores by AOFAS Members

Abstract: Most respondents preferred using the AOFAS Ankle score. The use of the empirical AOFAS Ankle score continues among AOFAS members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 16 publications
2
38
0
1
Order By: Relevance
“…46 It has been shown that the AOFAS ankle score is a valuable and clinically recognized functional score to assess ankle OA and other ankle disorders. 23,47,48 The AOFAS ankle scores in the present study are comparable to results of previous reports on ankle OA. 48 This study showed that AOFAS ankle scores were correlated with torque and EMG measurements.…”
Section: Discussionsupporting
confidence: 82%
“…46 It has been shown that the AOFAS ankle score is a valuable and clinically recognized functional score to assess ankle OA and other ankle disorders. 23,47,48 The AOFAS ankle scores in the present study are comparable to results of previous reports on ankle OA. 48 This study showed that AOFAS ankle scores were correlated with torque and EMG measurements.…”
Section: Discussionsupporting
confidence: 82%
“…preference of ankle outcomes scores. 29 In this study, the authors utilized an e-mail-based survey, with a response rate of 18% (107 of 589 members), lower than the 29% response rate of the current study.…”
Section: Discussionmentioning
confidence: 86%
“…AOFAS score [6] is the most commonly used scoring system for assessment of ankle problems [7]. VAS is a standard measurement tool in pain research and clinical practice [10].…”
Section: Methodsmentioning
confidence: 99%